Testing the CAPM With Time-Varying Risks and Returns. - Bodurtha, James N; Mark, Nelson C (Journal of Finance, 1991)
This paper draws on Robert F. Engle's autoregressive conditionally heteroskedastic modeling strategy to formulate a conditional capital asset pricing model with time-varying risk and expected returns. The model is estimated by generalized method of moments. A capital asset pricing model that allows mean excess returns to shift in January survives generalized method of moments specification tests for a number of omitted variables. However, a residual dividend yield component is found to remain in the excess returns of smaller firms. The authors find significant monthly and quarterly components in the risk premia and beta estimates.